Surgery as a Potential Treatment Option for Patients With Stage III Small-Cell Lung Cancer: A Propensity Score Matching Analysis - Zhang, Chenyue; Li, Cheng; Shang, Xiaoling; Lin, Jiamao; Wang, Haiyong (Frontiers in Oncology, 2019)
Surgery is commonly recommended for patients with stage I small-cell lung cancer (SCLC), whereas chemotherapy and radiotherapy are considered the standard treatment for patients with stage III SCLC. However, recent studies have suggested that a small proportion of patients with SCLC at an advanced stage may benefit from surgical resection. Therefore, in this study, we investigated the effectiveness of surgery in patients with stage III SCLC. Patients were selected from the Surveillance, Epidemiology, and End Results (SEER) database between 2004 and 2013. Propensity score matching (PSM) was used to eliminate any clinical bias. The overall survival (OS) was determined using the Kaplan–Meier method and compared using the log-rank test. The Cox proportional-hazards model was used to identify the effect of surgery on the OS. Of 9606 patients with stage III SCLC, 234 underwent surgery. Compared with the non-surgical group, a higher proportion of patients undergoing surgery had T1 and N0-N1 disease (risen by 10.7% for T1; 12.6% for N0-N1) and a lower proportion had T4 and N3 disease (decreased by 14.3% for T4; 12.5% for N3). The Kaplan-Meier analysis showed that patients who underwent surgery had a better OS before and after PSM. The multivariate analysis showed that surgery was beneficial for patients with stage III SCLC (HR: 0.651, 95% CI 0.524–0.808, P < 0.001). In conclusion, surgical resection might be associated with improved OS for patients with stage III SCLC and may be considered for the treatment of these patients. Further prospective studies are required to confirm these findings.